1999
DOI: 10.1002/(sici)1096-9837(199909)24:10<897::aid-esp18>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Gravel sediment routing from widespread, low- intensity landscape disturbance, Current River Basin, Missouri

Abstract: During the last 160 years, land‐use changes in the Ozarks have had the potential to cause widespread, low‐intensity delivery of excess amounts of gravel‐sized sediment to stream channels. Previous studies have indicated that this excess gravel bedload is moving in wave‐like forms through Ozarks drainage basins. The longitudinal, areal distribution of gravel bars along 160 km of the Current River, Missouri, was evaluated to determine the relative effects of valley‐scale controls, tributary basin characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 18 publications
1
31
1
Order By: Relevance
“…We think that the most important challenge is to understand sediment routing through the channel network. This can be achieved through both the development of theoretical tools that address this spatial scale (Benda and Dunne, 1997;Sklar et al, 2006) and field observations and measurements of channel responses to disturbed sediment regimes in adjusting river systems (Jacobson and Gran, 1999;Kasai et al, 2004). It is the confrontation of such approaches that will give us the opportunity to develop and test decision-making tools adapted for the integrative management of fluvial systems.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…We think that the most important challenge is to understand sediment routing through the channel network. This can be achieved through both the development of theoretical tools that address this spatial scale (Benda and Dunne, 1997;Sklar et al, 2006) and field observations and measurements of channel responses to disturbed sediment regimes in adjusting river systems (Jacobson and Gran, 1999;Kasai et al, 2004). It is the confrontation of such approaches that will give us the opportunity to develop and test decision-making tools adapted for the integrative management of fluvial systems.…”
Section: Resultssupporting
confidence: 61%
“…landslides and bank erosion). Thus, in some catchments, it has been demonstrated that tributaries only have a small effect on the longitudinal patterns of main-stem morphology and sedimentology, these patterns being mostly controlled by the processes of sediment-wave propagation through the drainage network (Jacobson and Gran, 1999). The diachronic study of the changing nature of tributaries is presented as a possible approach for evaluating their geomorphic impact.…”
Section: Resultsmentioning
confidence: 68%
“…In gravel-bed streams the downstream fining of bed material does not always occur orderly because of the influence of tributaries, large woody debris, and colluvial deposits (Dawson, 1988;Rice and Church, 1996;Powell, 1998). Land use disturbance in the Missouri Ozark Highlands is responsible for increased sediment in select basins, which has led to increased sediment routing through the system (Jacobson and Gran, 1999).…”
Section: Longitudinal Trends In Channel Morphologymentioning
confidence: 99%
“…The slugs may be generated through riverbed or bank erosion (endoslugs), or they may be formed by sediments from sources external to the river (exoslugs); furthermore, they may be associated with minor (macroslugs) or major (megaslugs) channel changes, or a major valley-floor adjustment (superslugs) (Nicholas et al, 1995). For example, in single-thread, gravel-bed rivers the process-form interaction between deposited bars and channel banks may lead to bank erosion (Nicholas et al, 1995;Wathen and Hoey, 1998;Klösch et al, 2015) and result in an increased local channel instability leading to the increased remobilization of floodplain sediments (Jacobson and Gran, 1999), causing channel widening or shallowing (Hoey, 1994;Wathen and Hoey, 1998;Klösch et al, 2015) and bend initiation (Leopold et al, 1964). This bar-bank interaction, in turn, may increase the magnitude of the initial sediment forms (Wathen and Hoey, 1998;Klösch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%